Occurrence of greedy scale, Hemiberlesia rapax (Comstock) (Hemiptera: Diaspididae), on mahogany in Brazil - Marcelo Tavares de Castro (Pesquisa Agropecuária Gaúcha, 2020)
The Brazilian mahogany (Swietenia macrophylla King, Meliaceae) is an important forest species known worldwide for the high commercial value of its wood. Few arthropods have been observed associated with mahogany. However, this paper reports the occurrence of Hemiberlesia rapax (Comstock) (Hemiptera: Diaspididae) in S. macrophylla plants for the first time. The greedy scales did not cause apparent damage on the trunks and petioles, but the leaves turned yellowish, dried, and fall prematurely. This is the first reported occurrence of H. rapax in S. macrophylla in the world.